Analysis of the Effectiveness of Traffic Flow Diversion on Road Performance: A Case of Jalan Gajah Mada Development Project, Batam - M Alfi Wahyudi; Andri Irfan Rifai; Joewono Prasetijo (International Journal Labs, 2022)
Indonesia is a country that is included in the top 5 rankings as the country with the most Population, with a population of 276 million people. Jalan Gajah Mada is one arterial road in Sekupang District, Batam City. Jalan Gajah Mada is often used to going to work and school. This has caused Jalan Gajah Mada to become one of the congestion points in Batam. This study aims to determine the effect of diverting cross-traffic flow on road performance during peak hours, namely morning or evening. The method used in this study is quantitative. The data used in this study consisted of primary data and secondary data. The primary data includes location conditions, road dimensions, number of vehicles, and vehicle speed. At the same time, the secondary data needed are the location map, data population, and land use. The location of the selected road performance analysis study. From the survey results, it can be concluded that Jalan Gajah Mada has a relatively good level of road service. The vehicle speed at the diversion of traffic flow is 48.78 Km/h, and the speed before the diversion of traffic flow is 26.16 Km/h.